2004
DOI: 10.1148/rg.241025713
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Breast Lymphoscintigraphy: Optimal Techniques for Performing Studies, Image Atlas, and Analysis of Images

Abstract: Breast lymphoscintigraphy is increasingly performed before surgery to delineate the drainage to the sentinel node (SN) in the axilla. On the basis of the histologic status of harvested SNs, the disease status of the entire axilla can be predicted. This prediction allows a more limited dissection to be performed while maintaining staging accuracy comparable with that of classic axillary lymph node dissection. Lymphoscintigraphy assists surgeons in harvesting the SN during gamma probe-assisted axillary biopsy or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 67 publications
1
76
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Koizumi et al 11 demonstrated enhancement of hot node detection by adding the anterior oblique 60° view to the anterior oblique 30° view for a tumor located at the upper lateral quadrant region. They suggested that multi-directional views contributed to depicting axillary nodes behind the injected radioactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Koizumi et al 11 demonstrated enhancement of hot node detection by adding the anterior oblique 60° view to the anterior oblique 30° view for a tumor located at the upper lateral quadrant region. They suggested that multi-directional views contributed to depicting axillary nodes behind the injected radioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Of many factors affecting the detection of SLN, patient positioning or choice of the best scintigraphic projection is one of the most important factors affecting satisfactory lymphoscintigraphic study. Sentinel node lymphoscintigraphy is usually obtained in a supine position, with the arm abducted completely to allow the head of the γ-camera to be placed as close as possible to the axilla.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed migration has the same finding specially in obese or old patients with reduced tracer migration from injection site to SLN (Krynyckyi et al, 2004;Goyal et al, 2006;Soran et al, 2007). This could be due to increased fatty tissue with impeding the flow of the tracer through the lymphatics or fatty degeneration of LNs reducing their capacity to concentrate the tracer.…”
Section: Discussionmentioning
confidence: 82%
“…Tissue attenuation and shine through effect of injection site are causes other than tumoral infiltration which lead to non-visualized SLN in lymphoscintigraphy but detected by intraoperative gamma probe (Krynyckyi et al, 2004). Delayed migration has the same finding specially in obese or old patients with reduced tracer migration from injection site to SLN (Krynyckyi et al, 2004;Goyal et al, 2006;Soran et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation